HUBUNGAN TINGKAT RELIGIUSITAS DENGAN SIKAP SEKSUAL NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II A WIROGUNAN YOGYAKARTA - , BIRRUL QODRIYYAH, Wenny Artanti Nisman, S.Kp, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Sexuality is human basic needs that expressed and experienced through sexual attitude. Prisoners often having barrier on expression of sexual fulfillment. Therefore contributes to the decicion of making sexual attitute. Objective: To investigate the correlation between religiosity and sexual attitudes, religiosity level overview and description of the sexual attitudes of prisoners in Lembaga Pemasyarakatan Kelas II A Wirogunan Yogyakarta.. Methods: This study was a cross-sectional quantitative study that conducted on 85 samples of a total population of 330 inmates who meet the criteria for inclusion